2022
DOI: 10.2147/ccid.s366979
|View full text |Cite
|
Sign up to set email alerts
|

Koji amazake Maintains Water Content in the Left Cheek Skin of Healthy Adults: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group, Comparative Trial

Abstract: Purpose Improvement in water content and skin barrier function on human skin is believed to be induced by koji amazake , a non-alcoholic beverage derived from rice fermented by Aspergillus oryzae ( A. oryzae ). In order to scientifically identify the effects of koji amazake on human skin, we performed a randomized, double-blind, placebo-controlled, parallel-group comparative trial and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several pieces of scientific research support these notions. For example, Rice- koji exerted increased water content in human skin [ 43 ], anti-aging effects in human dermal fibroblasts [ 44 ], and improvement in defecation frequency [ 2 ] and decreased blood pressure [ 45 ]. Of note, recent reports also demonstrated that rice-fermented foods can prevent adverse effects induced by psychological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several pieces of scientific research support these notions. For example, Rice- koji exerted increased water content in human skin [ 43 ], anti-aging effects in human dermal fibroblasts [ 44 ], and improvement in defecation frequency [ 2 ] and decreased blood pressure [ 45 ]. Of note, recent reports also demonstrated that rice-fermented foods can prevent adverse effects induced by psychological stress.…”
Section: Discussionmentioning
confidence: 99%